Health and working conditions of Swedish school teachers 1978 - Brenner, Sten-Olof (Karolinska Institutet, 2013)
The study 'Swedish teachers' health and well-being' is included in the project 'Work, health and well-being in teachers and school leaders in public school and in teachers in child care'. This research project is a part of a common Nordic project 'Work environment, health and well-being on teachers in public school in the Nordic Countries'. The Nordic Minister Counsellor's (Nordiska Ministerrådet) committee of officials for questions concerning working environment gave a mission to the Nordic researchers in 1975. The mission was to become united about a performance plan for a common Nordic project on psychosocial environment and health in working life. One of the two working groups which were elaborated as a suggestion was public school teachers.
The study 'Swedish public school teachers' health and well-being at work' was performed at 'the laboratory for clinical stress research' / 'the institute of psychosocial environmental health' at Karolinska Institute under the guidance of Sten-Olof Brenner. The project was completed in 1978 with a selection of respondents, arrangement and dispatch of questionnaires plus collection and processing of answers. A number of questions were asked to a random selection of public school teachers. The questions were asked to find out how the teachers experienced their working situation and how the working environment and the special character of the profession affect the teachers' health and well-being. The influence of the teacher's age, sex and other social backgrounds on the experience of work was examined. The different categories of teachers were compared to each other regarding how teaching in different phases and subjects affects the teacher's working environment.
The questionnaire included questions about serving and years of service, teaching in grades and subjects, the size of the classes and the number of teachers, the school's catchment area, timetabling, classes, discussions about teaching, school buildings and working premises, working environment issues, opinion about students, contact with other teachers, parental contact, contact with the school management, education, factors controlling work, anxiety and difficulties in work, support and help in work, appreciation and criticism in work, work related stress, leisure time, lack of time for leisure activities, health status and private situations.

Purpose:

The overall aim of the project was to find out how the teachers perceived their work situation, and how work environment and the character of the work affected teachers' health and well-being.

Studien Svenska grundskollärares hälsa och välbefinnande i arbetet ingår i projektet Arbete, hälsa och välbefinnande för lärare och skolledare inom grundskolan samt för lärare inom barnomsorgen. Detta forskningsprojekt ingår i ett nordiskt samarbetsprojekt Arbetsmiljö, hälsa och välbefinnande för lärare inom grundskolan i Norden. Nordiska ministerrådets ämbetsmannakommitte för arbetsmiljöfrågor gav år 1975 de nordiska stressforskarna i uppdrag att vid ett Nordstress-symposium försöka enas om en plan för att genomföra ett samnordiskt projekt om psykosocial miljö och hälsa inom arbetslivet. En av de två arbetstagargrupper som utarbetades till projektförslag var grundskollärare.

Studien Svenska grundskollärares hälsa och välbefinnande i arbetet genomfördes vid laboratoriet för klinisk stressforskning/institutionen för psykosocial miljömedicin vid Karolinska institutet under ledning av Sten-Olof Brenner. Projektet genomfördes år 1978 med urval av svarspersoner, uppläggning och utskickning av frågeformulär samt insamling och bearbetning av svar. I en enkätundersökning har man ställt ett antal frågor till ett slumpmässigt urval av grundskollärare. Man har genom frågorna velat få reda på hur lärarna upplever sin arbetssituation, om hur arbetsmiljön och arbetets speciella karaktär påverkar lärarnas hälsa och välbefinnande. Man vill också undersöka hur lärarens ålder, kön och annan social bakgrund påverkar lärarens upplevelse av arbetet. Man har också jämfört olika lärarkategorier med varandra beträffande hur undervisning i olika stadium och ämnen påverkar lärarens arbetsmiljö.

Enkäten innehöll frågor om tjänstgöring och tjänstgöringstid, undervisning i årskurser och ämnen, klassernas storlek och antal lärare, skolans upptagningsområde, schemaläggning, lektioner, klasser o dyl., diskussioner och sammanträden om undervisningen, skolbyggnad och arbetslokaler, arbetsmiljöproblem, uppfattning om elever, kontakt med andra lärare, kontakt med föräldrar, kontakt med skolledningen, utbildning, faktorer som styr arbetet, oro och svårigheter i arbetet, stöd och hjälp i arbetet, uppskattning och kritik i arbetet, påfrestningar i arbetet, fritid, brist på tid för fritidsaktiviteter, hälsotillstånd samt privata förhållanden.

Syfte:

Det övergripande syftet med projektet var att ta reda på hur lärarna upplevde sin arbetssituation, och hur arbetsmiljön och arbetets speciella karaktär påverkade lärarnas hälsa och välbefinnande.
Svenska grundskollärares hälsa och välbefinnande i arbetet 1978
Keywords: Work; Arbete; Workload; Arbetsbelastning; Job Satisfaction; Arbetstillfredsställelse; Leisure Activities; Fritidsaktiviteter; Health; Hälsa; Health Status; Hälsotillstånd; Environmental Exposure; Miljöexponering; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Disease; Sjukdom; Sick Leave; Sjukfrånvaro; Schools; Skolor; Social Environment; Social miljö; Social Support; Socialt stöd; Stress, Psychological; Psykologisk stress; Teaching; Undervisning; Occupations; Yrken; Occupational Exposure; Yrkesmässig exponering; Interprofessional Relations; Relationer inom yrkesgrupper; schoolteachers; skollärare; teachers; lärare; Working conditions; Arbetsförhållanden; Medical and Health Sciences; Medicin och hälsovetenskap; Occupational Health and Environmental Health; Arbetsmedicin och miljömedicin; HEALTH; HÄLSA; General health and well-being; Allmän hälsa och välbefinnande; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING